Relationship Between the Degree of Premenstrual Syndrome (PMS) among Female Students’s Haemoglobin levels - Wahyuni Dyah Parmasari; Dimas Ghani Ananda; Yunitati Maria Margaretha (Faculty of Medicine, Diponegoro University, 2025)
Background: Red blood cells include a protein called haemoglobin, which is responsible for transporting carbon dioxide gas (CO2) from the tissues back to the lungs and oxygen (O2) from the lungs to every part of the body. Low hemoglobin levels may impact numerous bodily functions related to hemoglobin. One of the symptoms of Premenstrual Syndrome (PMS) is menstrual pain, which low haemoglobin levels can bring on because they can reduce the amount of oxygen in the blood and stimulate the myometrium’s decreased blood flow. This leads to an increase in uterine muscle contraction. For one or two weeks before menstruation, women experience a collection of physical, emotional, and behavioural symptoms known as PMS, which arises during the luteal phase of the menstrual cycle. Students are generally in a transition phase where learning activities and imbalanced hormones trigger stress, thus worsening PMS levels.Objective: Determining the correlation between haemoglobin levels and the intensity of PMS in students. An observational analytical research design was used in this study. The group consisted of all students who met the inclusion and exclusion criteria and comprised the sample. To choose the sample, basic random sampling was employedMethods: An observational analytical research design was used to investigate. The analysis’s findings demonstrated a correlation between haemoglobin levels and the intensity of PMS among female students aged 20 to 23 years old enrolled in the Faculty of Medicine at Wijaya Kusuma University in Surabaya.Results: Haemoglobin levels and the severity of Premenstrual syndrome (PMS) among students were shown to be related, according to the analysis’s findings. The Spearman Correlation test sig result of 0,002 (<0,05) demonstrates this.Conclusion: This indicates a correlation between haemoglobin levels and the severity of PMS among female medical students in Wijaya Kusuma University of Surabaya.